The efficacy of vertical vs. horizontal plyometric training on speed, jumping performance and agility in soccer players - Manouras, N.; Papanikolaou, Z.; Karatrantou, K.; Kouvarakis, P.; Gerodimos, V. (International Journal of Sports Science & Coaching, 2016)
This study compared the efficacy of a vertical and horizontal plyometric training program on acceleration, speed, jumping performance, and agility in young soccer players during the in-season period. Thirty male soccer players (19.1±5.8 years) were assigned into a horizontal plyometric, a vertical plyometric, or a control group. The horizontal plyometric group and vertical plyometric group participated in an eight-week training program that was performed one day/week (in conjunction with conventional soccer training) and consisted of horizontal (for the horizontal plyometric group) or vertical plyometric exercises (for the vertical plyometric group). Acceleration (10-m sprint), speed (30-m sprint), agility, and jumping performance (horizontal and vertical) were assessed prior and after the completion of plyometric training programs. Agility, 30-m sprint performance, and vertical jumping performance (p<0.01) improved following the completion of training in both horizontal plyometric group and vertical plyometric group, whereas horizontal jumping performance improved only in horizontal plyometric group (p<0.01). There were no significant effects on acceleration for both horizontal plyometric group and vertical plyometric group. Furthermore, no differences were observed between groups in all performance parameters. In control group, acceleration, speed, agility, and jumping performance remained stable throughout the study. To sum up, horizontal or vertical plyometric training programs, consisted of one session/week, may be used by coaches and fitness professionals as effective exercise modalities for preserving or improving jumping performance, acceleration, speed, and agility in young soccer players during the in-season period. ABSTRACT FROM AUTHOR